The Effectiveness Of Virtual Laboratory Assisted Online Science Learning On The Scientific Character Of Elementary School Teachers Candidate - Setyo Eko Atmojo (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2022)
This study aims to analyze the effectiveness of online science learning assisted by a virtual laboratory on the scientific character of prospective elementary school teacher students. This scientific character is very much needed by prospective elementary school teachers to produce the next generation of the nation who master natural science and have good scientific character. This research method is an experiment with a quasi-experimental design type. The subjects of this study were students of classes A7 and A8, totaling 80 people. Data collection techniques using observation, questionnaires and tests. The data analysis technique used percentage, t-test, and N-gain. The results showed that there was an increase in the average appearance of scientific characters from each meeting from the medium level (54.55) at the first meeting to high (74.96) at the sixth meeting. The results of the t-test on the post-test score obtained that the t value = 2.798 > t table = 1.998 means that there is a significant difference in learning achievement between students who take online science learning assisted by virtual laboratories and students who take regular online science lessons. Based on the N-Gain test, it is known that the experimental group has an improvement with moderate criteria (0.62) which is better than the control group with low improvement criteria (0.26).